The Evolution of the English Language: From Old English to Modern English - Allanova M. M. qizi (Лучшие интеллектуальные исследования, 2024)
This article explores the fascinating journey of the English language from its early roots in Old English to its current form as Modern English. It delves into the historical, social, and linguistic factors that have shaped the language over the centuries, highlighting key milestones and transformations.